(untitled) (Research, Society and Development, 2021)
Objective: We aim to investigate the correlation between the construction of perception of time and smartphone dependence in university students in Campina Grande - PB. Methodology: This was a quantitative and experimental cognitive psychology study. Using Google Forms platform, we applied: I-) Socioeconomic Questionnaire; II-) Smartphone Dependence Scale (SDS); III-) Standardized stimulus presentation (466 seconds) and IV-) Questionnaire on stimulus perception. Variables were analyzed by the Statistical Package for Social Sciences (SPSS) – version 20.0. Results: 155 students were included, 115 female (74.2%) and 40 male (25.8%), average of 21.5 years old. Students were divided into two groups, according to SDS: 41 (26.45%) had no smartphone dependency and 33 (21.29%) were dependent. The perception of duration of the stimulus was 409 seconds among students without dependence, and 523 seconds among the others (27.8% higher - was 409s for the stimulus presented, while that of the group with a high level of dependence was 523s (27.8% higher, p < 0.001). Conclusion: Students who were dependent on smartphone had a greater perception of time duration compared to the group without dependence.